2019
DOI: 10.1038/s41598-019-56648-9
|View full text |Cite
|
Sign up to set email alerts
|

Proton-transfer pathways in the mitochondrial S. cerevisiae cytochrome c oxidase

Abstract: In cytochrome c oxidase (CytcO) reduction of O2 to water is linked to uptake of eight protons from the negative side of the membrane: four are substrate protons used to form water and four are pumped across the membrane. In bacterial oxidases, the substrate protons are taken up through the K and the D proton pathways, while the pumped protons are transferred through the D pathway. On the basis of studies with CytcO isolated from bovine heart mitochondria, it was suggested that in mitochondrial CytcOs the pumpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
(50 reference statements)
0
10
0
Order By: Relevance
“…The structure and function of the K and D proton pathways have been studied in detail in bacterial A1-type Cy-tcOs, 129,130,137−150 and their involvement in proton uptake also confirmed for the S. cerevisiae mitochondrial CytcO. 151,152 The K pathway starts near Glu82 in subunit II at the membrane n side (Figure 5B). It is connected via a water molecule to Ser256, which is hydrogen-bonded to the conserved Lys319.…”
Section: The Catalytic Reaction and Proton Pathwaysmentioning
confidence: 81%
See 1 more Smart Citation
“…The structure and function of the K and D proton pathways have been studied in detail in bacterial A1-type Cy-tcOs, 129,130,137−150 and their involvement in proton uptake also confirmed for the S. cerevisiae mitochondrial CytcO. 151,152 The K pathway starts near Glu82 in subunit II at the membrane n side (Figure 5B). It is connected via a water molecule to Ser256, which is hydrogen-bonded to the conserved Lys319.…”
Section: The Catalytic Reaction and Proton Pathwaysmentioning
confidence: 81%
“…165 Structural analyses and data from functional studies of structural variants in which putative residues of the H pathway were modified in the mitochondrial S. cerevisiae CytcO do not support a functional role of this pathway. 151,152,166 Furthermore, key residues of the suggested H pathway are not present in CytcO from plant mitochondria, 32 which suggest that its involvement in proton pumping would have to be restricted to the mammalian CytcOs.…”
Section: The Catalytic Reaction and Proton Pathwaysmentioning
confidence: 99%
“…The inhibitory effects of T316K and E243D are consistent with observations in variants of the equivalent T359 of R. sphaeroides (38,39), as well as with E/D replacement of the residue equivalent to E243 in E. coli (40), P. denitrificans (31), and R. sphaeroides (41). We previously showed that yeast mutant I67N (42), for which no equivalent bacterial mutant has been studied, is likely to interfere directly with E243 function at the top of the D-channel (43,44) and to compromise substrate proton uptake (45,46). These effects clearly confirm the expected essential roles of the D-and K-pathways in catalysis.…”
Section: Discussionmentioning
confidence: 99%
“…Complex proton transfer pathways . The P-side of all CcOs has a tangled cluster of strongly interacting polar and protonatable residues that do not provide an obvious single exit path, although linear paths have been suggested ( Popović and Stuchebrukhov, 2005 ; Björck et al, 2019 ). The hydrogen bond network on the P-side of A- and B-type CcO, was analyzed using Monte Carlo sampling and network analysis ( Cai et al, 2018 ; Cai et al, 2020 ).…”
Section: Cytochrome C Oxidasementioning
confidence: 99%